Oleic Acid-Based Self Micro-Emulsifying Delivery System for Enhancing Antifungal Activities of Clotrimazole - Ting-Lun Yang; Chien-Ming Hsieh; Ling-Jei Meng; Tsuimin Tsai; Chin-Tin Chen (MDPI AG, 2022)
Due to the increasing rate of drug resistance in Candida spp., higher doses of antifungal agents are being used resulting in toxicity. Drug delivery systems have been shown to provide an effective approach to enhance the efficacy and reduce the toxicity of antifungal agents. Oleic acid was revealed to effectively inhibit biofilm formation, hence reducing the virulence of Candida albicans. In this study, oleic acid-based self micro-emulsifying delivery systems (OA-SMEDDS) were developed for delivering clotrimazole (CLT). Based on the pseudo-ternary phase diagram and loading capacity test, the optimal ratio of OA-SMEDDS with CLT was selected. CLT-loaded OA-SMEDDS not only bears a higher drug loading capacity but also maintains good storage stability. The minimum inhibitory concentration (MIC50) of CLT-loaded OA-SMEDDS (0.01 μg/mL) in Candida albicans was significantly lower than that of CLT dissolved in DMSO (0.04 μg/mL). Moreover, we showed CLT-loaded OA-SMEDDS could effectively prevent biofilm formation and destroy the intact biofilm structure of Candida albicans. Furthermore, a CLT-loaded OA-SMEDDS gel was developed and evaluated for its antifungal properties. Disk diffusion assay indicated that both CLT-loaded OA-SMEDDS and CLT-loaded OA-SMEDDS gels were more effective than commercially available products in inhibiting the wild-type and drug-resistant species of Candida.